Kongolese Sacred Sovereignties and Legalities in the Early Modern Trans-Atlantic - Matthew Cavedon (Religions)
This article draws on political theology to provide a history of sovereignty (law-generating power) and legality (law-maintaining power) across an overlooked early modern trilogy of historical events. (1) The Kingdom of Kongo voluntarily adopted Catholicism in the late 1400s and early 1500s. Catholicism became a core part of its political identity and a major way through which Kongo resisted Portuguese exploitation and enslavement. However, Kongo’s compromises with Portuguese power gave rise to a heretical movement that triggered conflict, reforms, and mass enslavement and deportation. Some of those deported found themselves in South Carolina. (2) Deportees may have been part of a ditch-cutting crew at Stono that led the largest slave uprising in England’s mainland American colonies. Their Rebellion has many Kongolese characteristics and may have partly been a Kongolese Catholic response to English Protestantism. This is especially so because the rebels apparently meant to reach sanctuary in Spanish Florida. (3) Escapees from enslavement by Protestant rivals inspired Spain to offer freedom to fugitive slaves who converted to Catholicism. While Florida had a racial hierarchy and practiced slavery, its versions of these was somewhat milder due to religious and legal influences. Free Black people, especially escapees from the English, proved loyal subjects and militiamen—and Spain reciprocated with protection and inclusion. Chronicling sovereignty and legality across these three episodes is important for telling the history of how early Americans found the heart they needed to make their world less heartless.